2014
DOI: 10.1259/bjr.20140014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between human and model observer performance in low-contrast detection tasks in CT images: application to images reconstructed with filtered back projection and iterative algorithms

Abstract: RMS, Veldkamp WJH. Comparison between human and model observer performance in lowcontrast detection tasks in CT images: application to images reconstructed with filtered back projection and iterative algorithms. Br J Radiol 2014;87:20140014. FULL PAPERComparison between human and model observer performance in low-contrast detection tasks in CT images: application to images reconstructed with filtered back projection and iterative algorithms Objective: To compare low-contrast detectability (LCDet) perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…Several LCD phantoms are commercially available and were previously used for task‐based image quality assessment 2–4 . The ACR accreditation phantom (Gammex, Middleton, WI) contains cylinders of 2 to 25 mm diameter and 6 HU contrast.…”
Section: Introductionmentioning
confidence: 99%
“…Several LCD phantoms are commercially available and were previously used for task‐based image quality assessment 2–4 . The ACR accreditation phantom (Gammex, Middleton, WI) contains cylinders of 2 to 25 mm diameter and 6 HU contrast.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Several previous studies have demonstrated a good correlation between the performance of human observer and model observer. [17][18][19][21][22][23] Most of these studies were performed using phantoms with uniform background due to simplicity and availability of these phantoms. However, to assess image quality and radiation dose reduction in clinical CT imaging, physical phantoms having realistic background textures and lesions are highly desirable as the performance of reconstruction algorithms may be affected by anatomic background (i.e., structured noise).…”
Section: Introductionmentioning
confidence: 99%
“…Four-alternative forced-choice (4-AFC) [ 13 ] test was executed to evaluate low-contrast spatial resolution by five radiologists with at least 15 years of experience in clinical CT and four experienced radiology technicians [ 14 ]. Observers were trained on all technical aspects and objectives of the study and frontal training was performed through examples before the test.…”
Section: Methodsmentioning
confidence: 99%